MRI of synovitis and joint fluid. Issue 6 (8th January 2019) - Burke, Christopher J.; Alizai, Hamza; Beltran, Luis S; Regatte, Ravinder R.
Abstract : Synovitis and joint effusion are common manifestations of rheumatic disease and play an important role in the disease pathophysiology. Earlier detection and accurate assessment of synovial pathology, therefore, can facilitate appropriate clinical management and hence improve prognosis. Magnetic resonance imaging (MRI) allows unparalleled assessment of all joint structures and associated pathology. It has emerged as a powerful tool, which enables not only detection of synovitis and effusion, but also allows quantification, detailed characterization, and noninvasive monitoring of synovial processes. The purpose of this article is to summarize the pathophysiology of synovitis and to review the role of qualitative, semiquantitative, and quantitative MRI in the assessment of synovitis and joint fluid. We also discuss the utility of MRI as an outcome measure to assess treatment response, particularly with respect to osteoarthritis and rheumatoid arthritis. Emerging applications such as hybrid positron emission tomography / MRI and molecular imaging are also briefly discussed. Level of Evidence : 5 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2019.